Prevalence and molecular characterization of Anaplasmataceae agents in free-ranging Brazilian marsh deer (Blastocerus dichotomus) - Sacchi, A. B. V. [UNESP]; Duarte, J. M B [UNESP]; Andre, M. R. [UNESP]; Machado, R. Z. (Elsevier B.V., 2012)
Anaplasmataceae organisms comprise a group of obligate intracellular gram-negative, tick-borne bacteria that can infect both animals and humans. In the present work we investigate the presence of Ehrlichia, Anaplasrna, and Neorickettsia species in blood samples from Brazilian marsh deer (Blastocerus dichotomus), using both molecular and serologic techniques. Blood was collected from 143 deer captured along floodplains of the Parana River, near the Porto Primavera hydroelectric power plant. Before and after flooding, marsh deer were captured for a wide range research program under the financial support of São Paulo State Energy Company (CESP), between 1998 and 2001. Samples were divided into four groups according to time and location of capture and named MS01 (n = 99), MS02 (n = 18) (Mato Grosso do Sul, before and after flooding, respectively), PX (n = 9; Peixe River, after flooding), and AGUA (n = 17; Aguapei River, after flooding). The seroprevalences for Ehrlichia chaffeensis and Anaplasma phagocytophilum were 76.76% and 20.2% in MS01, 88.88% and 5.55% in MS02, 88.88% and 22.22% in PX, and 94.12% and 5.88% in AGUA, respectively. Sixty-one animals (42.65% of the total population) were PCR-positive for E. chaffeensis PCR (100.0% identity based on 16S rRNA, dsb, and groESL genes). Seventy deer (48.95% of the total population) were PCR-positive for Anaplasma spp. (99.0% of identity with A. platys, and in the same clade as A. phagocytophilum, A. bovis, and A. platys based on 16S rRNA phylogenetic analysis). Our results demonstrate that Brazilian marsh deer are exposed to E. chaffeensis and Anaplasma spp. and may act as reservoirs for these rickettsial agents, playing a role in disease transmission to humans and other animals. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Marsh deer (Blastocerus dichotomus); Ehrlichia chaffeensis; Anaplasma spp.; Brazil